2022
DOI: 10.3390/polym14102124
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Equations for Analyzing Stress Relaxation and Creep of Viscoelastic Materials Based on Standard Linear Solid Model Derived with Finite Loading Rate

Abstract: The viscoelastic properties of materials such as polymers can be quantitatively evaluated by measuring and analyzing the viscoelastic behaviors such as stress relaxation and creep. The standard linear solid model is a classical and commonly used mathematical model for analyzing stress relaxation and creep behaviors. Traditionally, the constitutive equations for analyzing stress relaxation and creep behaviors based on the standard linear solid model are derived using the assumption that the loading is a step fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 95 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…The NVB properties were analysed according to the Maxwell form of the Standard Linear Solid (SLS) model. The SLS is a popular viscoelastic model that is widely used due to its simplicity and high applicability; it models the elastic and viscous properties of a material using springs and dashpots that act in series and parallel with each other 17 . The springs capture the material's elastic response and the dashpots capture the dampening of the load, allowing for stress and strain to be modelled in time 17 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NVB properties were analysed according to the Maxwell form of the Standard Linear Solid (SLS) model. The SLS is a popular viscoelastic model that is widely used due to its simplicity and high applicability; it models the elastic and viscous properties of a material using springs and dashpots that act in series and parallel with each other 17 . The springs capture the material's elastic response and the dashpots capture the dampening of the load, allowing for stress and strain to be modelled in time 17 .…”
Section: Methodsmentioning
confidence: 99%
“…The SLS is a popular viscoelastic model that is widely used due to its simplicity and high applicability; it models the elastic and viscous properties of a material using springs and dashpots that act in series and parallel with each other 17 . The springs capture the material's elastic response and the dashpots capture the dampening of the load, allowing for stress and strain to be modelled in time 17 . The SLS model has been widely used to analyse the mechanical properties of polymers, hydrogels, blood vessels and cartilage 17 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows an example of the frequency sweep curve, where it can be observed that when the tip indents the sample in the first seconds, the sample presents creep and stress relaxation as a function of time. However, although viscoelastic materials such as cells present creep and stress relaxation, these parameters were not analyzed in this work [ 20 ].…”
Section: Methodsmentioning
confidence: 99%